Second line therapy in type 2 diabetes: legacy effect activation - Ekaterina A. Shestakova (Endocrinology Research Centre, 2017)
Type 2 diabetes causes hundred thousand deaths worldwide every year. Though new antidiabetic drugs appear annually and new classes of drugs are invented approximately every ten years still a lot of type 2 diabetic patients remain to be out of the target glycemic levels. According to most of the guidelines for type 2 diabetes,treatment metformin is the first line therapy for this disease. The choice of second-line antidiabetic drug usually depends on doctors’ preference. That is why defining the correct drug for exact patient is still an urgent question. This review provides data on antidiabetic drugspotential for preventing the progression of micro- and macrovascular complications.The question of the potential of early antidiabetic therapy intensification to activate legacy effect is debated. Early and lasting compensation of diabetes with the use of multiple drugs can become a basis for primary prevention of cardiovascular disease in such patients.